(untitled) (World Economics and Finance Bulletin, 2023)
The main reason for the growing demand for tourism services in the world is primarily socio-economic reasons, ie an increase in funds in the hands of the population, an increase in free time, an extension of the vacation period provided to employees and the expansion of such opportunities. Also, an increase in the development of transport, its cheapness and accessibility, a reduction or abolition of currency restrictions, liberalization of the visa regime, etc.